2018
DOI: 10.1111/ijfs.13930
|View full text |Cite
|
Sign up to set email alerts
|

Amaranth functional cookies exert potential antithrombotic and antihypertensive activities

Abstract: In this study, amaranth flour was used as an ingredient to prepare gluten-free cookies. The production process and attributes of amaranth cookies were characterised, and the potential use of amaranth flour as a functional ingredient was analysed. Cookies exhibited a non-uniform reddish brown colour and a cookie factor ratio of 4.5 AE 0.6. Storage studies indicated that after 3 weeks at room temperature cookies presented slight variations in the texture. Simulated gastrointestinal digestion of this product was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 27 publications
0
14
0
1
Order By: Relevance
“…Since supplemented pastes contain a significant amount of amaranth protein concentrate, both the proteins present in it and other components could contribute to the result achieved. Sabbione et al (2018)\ formulated amaranth flour cookies that are suitable for vegan and gluten-free diets and with adequate physicochemical and sensory characteristics. The cookies provide 114 Kcal per 30 g serving.…”
Section: Functional Foodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since supplemented pastes contain a significant amount of amaranth protein concentrate, both the proteins present in it and other components could contribute to the result achieved. Sabbione et al (2018)\ formulated amaranth flour cookies that are suitable for vegan and gluten-free diets and with adequate physicochemical and sensory characteristics. The cookies provide 114 Kcal per 30 g serving.…”
Section: Functional Foodsmentioning
confidence: 99%
“… Sabbione et al. (2018) \ formulated amaranth flour cookies that are suitable for vegan and gluten-free diets and with adequate physicochemical and sensory characteristics.…”
Section: Functional Foodsmentioning
confidence: 99%
“…A intolerância ao glúten causa a doença celíaca, uma doença autoimune caracterizada por resultar em lesões na mucosa do intestino delgado, o que acarreta o desenvolvimento de atrofia total ou parcial das vilosidades e, posteriormente, em má absorção de nutrientes. A doença celíaca pode aparecer em qualquer fase da vida, e estima-se que um, em cada 400 brasileiros, seja celíaco e que a cada oito pessoas com a doença celíaca, apenas uma possui o diagnóstico correto para a doença (BRASIL, 2013;KAGNOFF, 2005;SDEPANIAN;MORAIS;FAGUNDES-NETO, 2001).…”
Section: Introductionunclassified
“…Sabbione et al . presented their findings from a study into the use of amaranth flour for the production of cookies and their subsequent characterisation. In vitro digestion studies indicated that these functional cookies released peptides which had the potential to exert an antithrombotic and antihypertensive effect (Sabbione et al ., ).…”
mentioning
confidence: 99%
“…Sabbione et al . presented their findings from a study into the use of amaranth flour for the production of cookies and their subsequent characterisation. In vitro digestion studies indicated that these functional cookies released peptides which had the potential to exert an antithrombotic and antihypertensive effect (Sabbione et al ., ). The development of this type of snack food with healthy properties presents an enormous opportunity for manufacturers, as the market for snack‐type products continues to grow among consumers looking for healthy alternatives.…”
mentioning
confidence: 99%